INNOVATIVE INTERFACE OF RESEARCH AND EDUCATIONAL PROCESS: NATURE AND DEVELOPMENT PROSPECTS - Mikhail Alexandrovich Izotov; Besarion Chokhoyevich Meskhi (Advanced Engineering Research, 2012)
At the present stage of the Russian economy development, education in its extricable connection with science and production accommodates the efficiency and competitiveness of the national economy. In consequence of the interaction of the scientific research, design departments of the industrial enterprises and leading engineering universities, the integrated structures and a new approach to the transfer of the R&D results are formed. The challenges facing the university integrated package include not only the training of highly qualified specialists, but also the implementation of educational, research, and innovation projects. The analysis of modern models of the development of innovation corporate educational institutions shows that they are based on three key technologies: intelligent, management, and information ones. The innovative type of the development demands the comprehensive resources provision, and the economic systems stability, apart from the organizational prerequisites. The complexity of the resources provision is determined by the essential resource intensity of the innovation infrastructure processes. The interface acts both as a bonding technique, and as a place of innovative communication features, besides, its architecture as a whole is service-oriented.